Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

solve linear system using substitution

y=6-2x
7x-y=3


Sagot :

luana
[tex] \left \{ {{y=6-2x} \atop {7x-y=3}} \right. \\\\substitute\ first\ equation\ into\ the\ second\\\\ 7x-(6-2x)=3\\\\ 7x-6+2x=3\\\\ 9x-6=3\ \ \ | add\ 6\\\\ 9x=9\ \ \ | divide\ by\ 9\\\\ x=1\\\\ y=6-2*1=6-2=4[/tex]